Organizational culture influence towards decision-making process in public organizations - Hashim, Hizatul Haliza; Asmuni, Azizan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Decision-making is an important part of an organization daily activities and it occurs at every level in an organization. The types of decision-making process used in an organization act as a predictor of organizational effectiveness and significantly influence the success of an organization. It is also important to realize that the way managers make decisions and solve problems are influenced by organizational culture. However, there are slight differences in the way decisions are made in the public and private organizations. Public organizations experience more turbulence, interruptions, recycles and conflict decision-making process if compared to smoother decision-making process in the private and for profit organizations. In realizing the differences, this conceptual paper is about managerial decision-making process and how the process is influenced by its cultural values, particularly from the perspectives of public organizations.